PENDIDIKAN AKUNTANSI FORENSIK DAN INVESTIGASI PENIPUAN - Hasna Hanifah; Harti Budi Yanti (EBID: Ekonomi Bisnis Digital, 2023)
The high number of fraud casesthat have occurred in Indonesia, both in the financial and public sectors, has caused a lot of harm to the people of Indonesia, and is also a concern for the global world. The high cases  of  fraud  require  forensic  accountants  who  are  reliable  in  their  fields,  including  in  investigating fraud that occurs in a company/organization in Indonesia. This study describes several formulations of the  problem,  including  whether  forensic  accounting  affects  the  performance  of  the  forensic  auditor, whether  the  ability  offraud  investigations  affects  the  performance  of  the  forensic  auditor,  and  finally whether  the  experience  of  knowledge  and  skills  of  forensic  investigation.  This  research  has  important roles and implications for readers, especially for auditors, forensic accountants, and fraud investigators. The type of data collection technique used by researchers is primary data by distributing questionnaires to S1 Accounting students who are actively registered at universities in Indonesia. The results obtained in  this  study  are  that  Forensic  Accounting  Education  as  well  as  Fraud  Investigation  has  an  effect  on Forensic  Auditor  Performance.  The  researcher  recommends  to  future  researchers  to  implement  and develop the results of this study so that the results of this study are better.